THE PRATI DI STUORES/STUORES WIESEN SECTION (DOLOMITES, ITALY): A CANDIDATE GLOBAL STRATOTYPE SECTION AND POINT FOR THE BASE OF THE CARNIAN STAGE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
The Prati di Stuores/Stuores Wiesen section (Dolomites, Italy) is proposed as a candidate Global Stratotype Section and Point for the base of the Carnian Stage. In addition to being a famous, richly fossiliferous locality, it includes the type-section of the Cordevolian substage. The section is located near Pralongià, along the southern slope of the crest separating the Badia/Abtei and Cordevole valleys. Below the levels with Trachyceras aon, the section contains a rich ammonoid fauna that chacterizes the lower part of the Regoledanus Subzone and subsequently records the first appearances of the mid-high latitude genus Daxatina (Daxatina sp., D. cf. canadensis) and of traditional Trachyceras with species different from T. aon. Moreover, the Daxatina cf. canadensis Subzone is recognised above the Regoledanus Subzone. Very rare conodonts of the Budurovignatus group and species of Gladigondolella from the diebeli Assemblage Zone occur. Gondolella polygnatyformis, already known from the Aon Subzone, is absent. Palynomorphs, foraminifers, gastropods, bivalves, brachiopods, microcrinoids and holothurian sclerites were studied. Variations in frequency and taxonomic diversity of these faunas suggest anaerobic-disaerobic bottom conditions for the lower-middle part of the section (0-105 m), followed by a more stable oxygen content in the upper portion. Magnetostratigraphy showed four intervals with normal polarity and three intervals with reversed polarity. The Daxatina cf. canadensis Subzone falls close to the normal polarity interval S2n. The present study proposes the FAD of the cosmopolitan genus Daxatina as a marker of the base of the Carnian Stage, placing it at a lower stratigraphic level than previously indicated in the Stuores area. The Prati di Stuores section is proposed as GSSP of the Ladinian-Carnian boundary.